CRITICAL REVIEW OF SPENGLER’S POLITICAL BOOK “PRUSSIANISM AND SOCIALISM” - Gajic, Aleksandar (National interest, 2025)
The Paper provides a critical review of Spengler’s most famous political book “Prussianism and Socialism” confronting it with the fundamental theses presented in Spengler’s main work, “Decline of the West” and questioning the (un)realization of some predictions from a distance longer than a century. The first part of the Paper gives a cross-section through the fundamental theses presented in the book “Prussianism and Socialism” such as the futility of the German revolution of 1918, the opposition between English and Prussian spirit in the Western world, “English” nature of Marxist socialism, etc. The central part of the Paper provides a critical account of the phenomenon of socialism from the perspective of Spengler’s cultural morphology and the role of the Prussians and the Romans in his comparative historical analysis. The final part of the paper synthesizes critical conclusions. It explains the erroneous assessments and forecasts Spengler made in his political writings regarding the relationship between Prussia and socialism. Spengler mistakenly identified socialism as a modern aspiration towards unity with bureaucratic, hierarchical modifications of the social order (a characteristic not only of the Prussians but of all peoples whose societies and states in these modernization processes are becoming more complex based on their cultural heritage). However, in "The Decline of the West," he correctly observed the mixture of rational moralism and nihilism as the basis for "socialisms" in various cultures throughout history—from this error followed the next: the identification of the Prussians with the Romans and their fate of "adopting" and modifying socialism for the doctrinal justification of their imperialism. Historical events, that is, Germany’s failure to achieve its imperial mission and the fact that only America has an imperial role in the Western world, in Spengler’s interpretation of historical events, have the force of a final verdict: it is not Prussia, but America that has/will appropriate socialism for its imperial goals and among whom "new Caesars" will emerge who will solidify the Western imperial order.